Mahi the story of India's most successful captain - Guha Ray, Shantanu (New Delhi Lotus Collection, 2013)
On Mahendra Singh Dhoni, b. 1981, Indian cricketer.
Includes index.
Keywords: Dhoni, Mahendra Singh, -- 1981-; Cricket captains -- India -- Biography; Cricket players -- India -- Biography